Online-to-offline platforms: examining the effects of demand-side usage on supply-side decisions - Wan, Xing (2023)
This study explores the impact of demand-side usage of digital platforms on operational decision-making by supply-side firms. The positive impact of digital platforms on product sales is established in the literature. However, this study focuses on the perspective of supply-side firms, examining the effect of increasing reliance on digital platforms on supply-side firms’ decisions. The study shows that greater demand-side usage of online-to-offline (O2O) digital platforms is associated with more efficient operational decisions of supply-side firms. Benefits of leveraging O2O platforms include information transparency and resource pooling. The study further examines the extent to which benefits from participating in O2O digital platforms are affected by inter-firm relationships in which a supply-side firm is embedded. The study uses a panel data model to test hypotheses with data on China's movie theaters that join O2O platforms. It found that movie theaters with greater demand-side usage of O2O digital platforms see better resource utilization and product concentration. Furthermore, it shows that more vertically integrated firms can better reap the benefits from demand-side usage of digital platforms. In contrast, more horizontally integrated firms can less strategically leverage the benefits from demand-side usage of O2O platforms.